Coupled two-fluid flow and wall heat conduction modeling of nucleate pool boiling. (3rd August 2021) - Petrovic, Milan M.; Stevanovic, Vladimir D.
Abstract: A new CFD modeling approach is developed and applied to a numerical study of pool boiling. It is based on a coupled simultaneous solving of the two-fluid model of two-phase flow in the boiling pool and the transient heat conduction within the heated wall. The applied two-fluid model consist in mass, momentum and energy balance equations for each phase and the closure laws for interface transport due to friction and phase transition. The boiling two-fluid mixture is thermally coupled with the heated wall by the heat transfer at the bubble footprint at randomly determined discrete locations of the nucleation sites and by the conjugate heat transfer from the heated wall to the wetting liquid on the surface outside the nucleation sites. The model is validated against detailed experimental data from the literature. Sensitivity analysis is performed to evaluate the influence of pool boiling parameters and conditions on the boiling curve, such as the nucleation site density, the wetting contact angle, the wall thermal conductivity, the wall thickness, the wall volumetric or bottom surface heating and the liquid volume in the pool. Temperature transients at the bubble nucleation sites are evaluated. The two-phase mixture pattern in pool boiling and the related swell level position can be well predicted with the nonuniform heat flux determined by the discrete nucleation sites of bubble growth and conjugate heat transfer from the heated wall to wetting liquid. The developed computational method is efficient and robust, while the reliability of its prediction is sensitive to the accuracy of nucleation site density and contact angle input data, as parameters that describe the coupled thermal and physical characteristics at the fluid-wall interface.